2018
DOI: 10.3390/app8050667
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mastic Asphalt Waterproofing Layer in High-Speed Railway Track in Cold Regions

Abstract: Abstract:Freeze-thaw damage is a typical distress incurred in road and railway engineering in cold regions. Concrete waterproofing layer is commonly used in high-speed railway tracks to prevent the penetration of surface water, however, it cracks easily under thermal stress, especially in cold regions. Recently solutions have been proposed to increase the waterproofing layer's cracking resistance by using asphalt layers. Nonetheless, the use of emulsified asphalt as well as dense-graded asphalt mixture were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…By setting partly and totally delaminated interface state as the initial conditions, the influence of interface damage on the dynamic response was also analyzed. The main findings can be summarized as follows (1) It is reasonable to obtain the parameters of CZM from the full-scale transverse shear test and apply them in the numerical simulations of interfacial damage evolution under temperature load. (2) For the simulated conditions in this work, the microcracks between CCBP and ACWL were initiated when the temperature rising range was 5.9 • C, and the adjacent layers started to delaminate when the heating range was 19.2 • C. When ∆t exceeded 60 • C, the interface totally delaminated and turned into the slipping contacting state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By setting partly and totally delaminated interface state as the initial conditions, the influence of interface damage on the dynamic response was also analyzed. The main findings can be summarized as follows (1) It is reasonable to obtain the parameters of CZM from the full-scale transverse shear test and apply them in the numerical simulations of interfacial damage evolution under temperature load. (2) For the simulated conditions in this work, the microcracks between CCBP and ACWL were initiated when the temperature rising range was 5.9 • C, and the adjacent layers started to delaminate when the heating range was 19.2 • C. When ∆t exceeded 60 • C, the interface totally delaminated and turned into the slipping contacting state.…”
Section: Discussionmentioning
confidence: 99%
“…Asphalt concrete has been tentatively used for a full-cross-section waterproofing layer in the substructure of ballastless track in China [1,2]. Asphalt concrete has also been employed as an isolation layer of the high-speed railway foundation, sub-ballast layer of ballast railway, or reinforcement layer of the railway subgrade in Germany, Japan, France, Italy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Shear and pull-off tests were conducted to evaluate the bond properties [19]. The shear test was divided into single shear and inclined shear tests according to whether there is positive pressure or not.…”
Section: Bonding Properties Of Steel/ecc Interfacementioning
confidence: 99%
“…Yusupov et al [10] have also presented a numerical study to examine and predicted the difference in asphalt behaviors at high temperatures, in the example of viscoelastic material assigned to the asphalt concrete trackbed. Liu et al [11] have studied the effect of mastic asphalt waterproofing layer in the railway structure and indicated that the mastic asphalt layer significantly contributes to the trackbed to be waterproof and thus could considerably reduce freeze-thaw damage risk.…”
Section: Introductionmentioning
confidence: 99%